Importance of Implementing Occupational Safety and Health Systems for Labor Protection in Industry - Agustin Vitaloka Ammelia Putri; Yoga Subekti Nugroho; Khairisma Amanda Chairunnisa; Ambar Cahyaning Rahma Danastuti; Mohammad Ryan Effendi Saputra; Ramadhan Guntur Widodo (Proceeding International Conference Restructuring and Transforming Law, 2022)
Occupational safety and health is one aspect of labor protection regulated in Law No. 13 of 2003. By implementing occupational safety and health control technology, it is hoped that the workforce will achieve physical resilience, work power, and a high level of health. Of the occupational safety and health management system are: Managing organizational activities to reduce or eliminate the risk of work accidents Experienced by members of the organization for work safety and comfort, so as to achieve organizational goals effectively. Occupational safety and health management system. The role of occupational safety and health is very necessary in order to provide protection for workers, as regulated in Law Number 13 of 2003 concerning Manpower.